2000
DOI: 10.1128/mmbr.64.4.746-785.2000
|View full text |Cite
|
Sign up to set email alerts
|

Signal Transduction Cascades Regulating Fungal Development and Virulence

Abstract: SUMMARY Cellular differentiation, mating, and filamentous growth are regulated in many fungi by environmental and nutritional signals. For example, in response to nitrogen limitation, diploid cells of the yeast Saccharomyces cerevisiae undergo a dimorphic transition to filamentous growth referred to as pseudohyphal differentiation. Yeast filamentous growth is regulated, in part, by two conserved signal transduction cascades: a mitogen-activated protein kinase cascade and a G-protein regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
788
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 837 publications
(803 citation statements)
references
References 341 publications
(491 reference statements)
10
788
0
5
Order By: Relevance
“…46 MendesGiannini et al 47 observed a relationship between virulence and adherence to the ECM when comparing several P. brasiliensis isolates that showed different levels of virulence in vivo; the authors demonstrated that the isolate Pb18, which was recently isolated from an animal, had a greater ability to adhere to ECM components. Confirming the results of Andreotti et al, 2005, 27 we demonstrated that low expression of Pb14-3-3 resulted in a reduction of binding to laminin; this interaction was assessed by ELISA, which has greater sensitivity and specificity than the immunoblotting that was performed in the study cited above.…”
Section: Discussionmentioning
confidence: 99%
“…46 MendesGiannini et al 47 observed a relationship between virulence and adherence to the ECM when comparing several P. brasiliensis isolates that showed different levels of virulence in vivo; the authors demonstrated that the isolate Pb18, which was recently isolated from an animal, had a greater ability to adhere to ECM components. Confirming the results of Andreotti et al, 2005, 27 we demonstrated that low expression of Pb14-3-3 resulted in a reduction of binding to laminin; this interaction was assessed by ELISA, which has greater sensitivity and specificity than the immunoblotting that was performed in the study cited above.…”
Section: Discussionmentioning
confidence: 99%
“…Core elements of MAPK and calcium signalling pathways are required for virulence in a wide array of fungal pathogens of plants and mammals (Kraus and Heitman, 2003;Lee et al, 2003;Lengeler et al, 2000;Zhao et al, 2007). Such a degree of functional conservation is remarkable, considering the taxonomic and biological diversity among these pathogens, but also raises a number of questions regarding the specific role of these pathways in fungal infection.…”
Section: Introductionmentioning
confidence: 99%
“…In C. albicans, filamentation is also induced under nitrogenstarvation conditions and by activation of MAPK and PKA pathways. However, unlike S. cerevisiae, in addition to nutrient starvation multiple in vitro conditions can induce filamentation, including pH, temperature, serum and embedment in agar (reviewed by Berman & Sudbery, 2002;Brown, 2002;Lengeler et al, 2000). In this study several induction methods were tested and Bmh1p was involved in all instances.…”
Section: Discussionmentioning
confidence: 99%